2017
DOI: 10.1038/s41598-017-04138-1
|View full text |Cite
|
Sign up to set email alerts
|

Viperin is an important host restriction factor in control of Zika virus infection

Abstract: Zika virus (ZIKV) infection has emerged as a global health threat and infection of pregnant women causes intrauterine growth restriction, spontaneous abortion and microcephaly in newborns. Here we show using biologically relevant cells of neural and placental origin that following ZIKV infection, there is attenuation of the cellular innate response characterised by reduced expression of IFN-β and associated interferon stimulated genes (ISGs). One such ISG is viperin that has well documented antiviral activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 55 publications
9
102
0
Order By: Relevance
“…TLR7 is expressed in monocytes, MDMs and plasmacytoid DCs and in B cells (Hornung, Rothenfusser et al 2002, Gantier, Tong et al 2008) while TLR8 is expressed in monocytes, MDMs and myeloid DCs (Hornung, Rothenfusser et al 2002, Alexopoulou, Desnues et al 2012). Analysis of a panel of mutated viperin proteins showed that the carboxy-terminus of the protein was required for antiviral activity, consistent with the findings of Van der Hoek et al who showed that viperin restricts ZIKV replication in Huh7 cells and that virus replication is enhanced in viperin knockout mouse embryonic fibroblasts (Van der Hoek, Eyre et al 2017). …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…TLR7 is expressed in monocytes, MDMs and plasmacytoid DCs and in B cells (Hornung, Rothenfusser et al 2002, Gantier, Tong et al 2008) while TLR8 is expressed in monocytes, MDMs and myeloid DCs (Hornung, Rothenfusser et al 2002, Alexopoulou, Desnues et al 2012). Analysis of a panel of mutated viperin proteins showed that the carboxy-terminus of the protein was required for antiviral activity, consistent with the findings of Van der Hoek et al who showed that viperin restricts ZIKV replication in Huh7 cells and that virus replication is enhanced in viperin knockout mouse embryonic fibroblasts (Van der Hoek, Eyre et al 2017). …”
Section: Discussionsupporting
confidence: 83%
“…To test the ability of CHME3 cells to support ZIKV replication, we infected them and after 24h quantified intracellular viral RNA and compared the results to blood-derived monocytes and MDMs infected in parallel (Foo, Chen et al 2017, Van der Hoek, Eyre et al 2017). CHME3 cells supported robust ZIKV replication, replicating to a level comparable to that in monocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the IFN-induced transmembrane proteins, IFITM2 and IFITM3, have been shown to restrict infection at early stages of the viral life cycle and provide protection against ZIKV-induced cytopathic effects in HeLa cells [10]. Additionally, viperin, another antiviral ISG, is able to restrict replication in human hepatoma cells; and viperin knockout mouse embryonic fibroblast cells produce higher ZIKV titers than wild-type cells [11]. However, viperin induction was comparatively low in human cells of placental or neural origin upon infection, highlighting the cell-specific nature of ZIKV-induced ISG expression, which is likely influenced by both viral suppression as well as differences in host intrinsic factors [11].…”
Section: Type I Ifn Stimulated Genes Restrict Zikv Infectionmentioning
confidence: 99%
“…Additionally, viperin, another antiviral ISG, is able to restrict replication in human hepatoma cells; and viperin knockout mouse embryonic fibroblast cells produce higher ZIKV titers than wild-type cells [11]. However, viperin induction was comparatively low in human cells of placental or neural origin upon infection, highlighting the cell-specific nature of ZIKV-induced ISG expression, which is likely influenced by both viral suppression as well as differences in host intrinsic factors [11]. Thus, in order to establish an infection, ZIKV must have evolved mechanisms to overcome type I IFN signaling and ISGs.…”
Section: Type I Ifn Stimulated Genes Restrict Zikv Infectionmentioning
confidence: 99%